1975
DOI: 10.1148/15.3.687
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Therapy of Brain Tumors in Children

Abstract: The case histories of 124 children irradiated for brain tumors were reviewed to determine survival rate and functional prognosis, with special reference to somatic growth. Five-year survival rates (29% of 97 patients with gliomas and 70% of 27 patients with non-gliomatous tumors) were approximately the same as in our adult series, despite the differences in histology and predilection. Although 70% of 42 long-term survivors had active, useful lives, stunted growth was observed in 15 of them. More attention shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1977
1977
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…The first case of induced hypopituitarism and growth retardation in children after cranial radiation for a tumor distant from the hypothalamic-pituitary region was reported in 1966 (4), and was followed quickly by several other reports (5)(6)(7)(8)(9)(10)(11)(12). It soon became apparent that irradiation of the hypothalamus and the pituitary gland resulted in a high incidence of G H deficiency and growth retardation.…”
Section: Growth Hormone Deficiencymentioning
confidence: 99%
“…The first case of induced hypopituitarism and growth retardation in children after cranial radiation for a tumor distant from the hypothalamic-pituitary region was reported in 1966 (4), and was followed quickly by several other reports (5)(6)(7)(8)(9)(10)(11)(12). It soon became apparent that irradiation of the hypothalamus and the pituitary gland resulted in a high incidence of G H deficiency and growth retardation.…”
Section: Growth Hormone Deficiencymentioning
confidence: 99%
“…[1,4,8,10,12,23,25] Radiation therapy is not without risk: there are case reports of malignant astrocytomas developing many years after radiation therapy in patients who had low-grade astrocytomas, [27,34] and the late development of meningiomas in the radiation field of treatment has also been observed at the Mayo Clinic at Rochester.…”
Section: Discussionmentioning
confidence: 99%
“…37 of the 56 patients showed an impaired GH response (peak <20 mU/l) and only I of these received less than 2,900 cGy, although data were lacking in the 2.500-2,900 cGy range, so that the dose required to affect GFI production may actually be lower than 2,900 cGy (over 3 weeks). Onoyama et al [8] observed stunted growth in 50% of their children who received more than 3,000 cGy to the hypothalamic-pituitary region. However, they did not provide any endocrine data on their patients and the numbers were small.…”
Section: Radiation-induced Gh Deficiencymentioning
confidence: 99%
“…These tumours include gliomas, ependymomas and medulloblastomas but not craniopharyngiomas. Short stature is an extremely common complication [1,8] following the treat ment of such tumours in childhood. Preliminary work [17] suggested that biochemical evidence of growth hormone (GH) deficiency was common in these children.…”
Section: Introductionmentioning
confidence: 99%